(untitled) (Ciudades, 2017)
After the bursting of the housing bubble in Spain seems that part of the real estate sector and its agents has joined those who criticized the model of indefinite growth to establish that protagonist of the new cycle should be intervention in the consolidated city. This article discusses the changes that have occurred in recent years and some of the key issues that should guide these interventions. We think that there is no universal solution to address the problems and needs of our neighbourhoods, and that public funding will be needed in much of urban areas in need of intervention.